Changes in the genus Beana Walker (Beaninae Zahiri & Holloway) with two new species and removing Beana nitida Tams to a new genus Beanoides (gen. nov.) - Pellinen, Markku J.; Wahlberg, Niklas (Zootaxa, 2021)
Two new Beana species (B. mutaneni sp. nov and B. penniuncus sp. nov) are described here. Based on molecular data, Beana nitida Tams is removed to its own genus Beanoides gen. nov. and placed in the subfamily Chloephorinae. Morphological characteristics and DNA barcodes are provided for the new species, with a comparison of morphological structures and genetic distances to Beana terminigera Walker. The current number of valid species in the genus is six.